Early pregnancy metal levels in maternal blood and pregnancy outcomes - Ifat Baram Goldberg; Eyal Sheiner; Maayan Hagbi Bal; Doron Bergman; Noam Tomasis Damri; Ron Rosenbaum; Ayal Haimov; Tamar Wainstock (Scientific Reports)
Abstract Prenatal exposure to heavy metals such as Lead (Pb), arsenic (As), cadmium (Cd), and selenium (Se) is associated with various adverse pregnancy outcomes. This study examines the association between early pregnancy maternal blood levels of these metals and adverse pregnancy outcomes, while also addressing the differences between low-risk and high-risk groups based on having a history of preterm birth (PTB). This prospective cohort study recruited parous women during first trimester, categorized into low-risk and high-risk groups. Participants completed a questionnaire, and heavy metal levels were measured in blood samples. Pregnancy outcomes including PTB, low birth weight (LBW), gestational age at delivery, birth weight and head circumference were recorded following delivery. Multivariable analyses were conducted to evaluate the independent associations between heavy metal levels and pregnancy outcomes, while adjusting for maternal age, BMI, employment, smoking, fertility treatments and education. Among 404 participants, the mean (± SD) levels were Pb: 3.12 ± 1.82 µg/L, As: 0.41 ± 0.4 µg/L, Cd: 0.26 ± 0.34 µg/L, and Se: 119.84 ± 21.05 µg/L. Significant differences in Pb, Se, Cd and As levels were observed between the low-risk and high-risk groups, with higher levels in the low-risk group. However, no significant associations were found between heavy metal levels and any of the study outcomes in either univariable comparison or multivariable models. These findings highlight the need for further research to understand the potential impact of these metals on pregnancy, considering population-specific factors and exposure timing.